Chosen synanthropic plant species in the Bug river valley: routes and effects of expansion - Marciniuk, Paweł; Wierzba, Marek (Biodiversity: Research and Conservation, 2006)
The relatively low degree of transformation of the Bug river valley is the reason of its low synanthropization. The distribution of 12 synanthropic species (kenophytes) was analysed in view of their expansion routes and both observed and predicted ecological effects of their expansion in the Bug valley. Acer negundo, Bidens frondosa and Xanthium albinum proved to be common in natural and semi-natural plant communities in the study area, but Solidago gigantea, Echinocystis lobata, Erigeron annuus and Bryonia alba are rare there. Heracleum mantegazzianum, Iva xanthiifolia, Parthenocissus inserata, Salix acutifolia and Lycium barbarum are invasive but mainly in ruderal sites. Interestingly, also the native Carex brizoides behaves like a kenophyte at forest edges in the Bug valley.